Development of interlayers based on polymethacrylate incorporating tertiary amine for organic solar cells with improved efficiency and stability - Park, So Hyun; Park, Sungmin; Lee, Keun Jun; Kim, Jai Kyeong; Son, Hae Jung (ELSEVIER SCI LTD, 2021)
Nonfullerene acceptors have played a critical role in achieving record efficiency of organic photovoltaic (OPV) devices, and ITIC-based materials are an important type of nonfullerene acceptor. Herein, we developed new interlayer polymers for nonfullerene acceptor-based OPVs: PDMA(N)EMA and PDMA (N-O)EMA. In particular, PDMA(N)EMA effectively lowered the work function at the interface with the bulk heterojunction active layer and thus enabled efficient electron collection by the OPV device. Therefore, the OPV device incorporating PDMA (N)EMA showed a power conversion efficiency (PCE) of 8.19%, which was substantially enhanced compared with the 4.54% PCE of an ethoxylated polyethylenimine (PEIE)-based device. Whereas PEIE chemically attacked ITIC and degraded the performance of the OPV device, the PDMA(N)EMA formed a stable interface with ITIC, resulting in a dramatic increase of the VOC of the PDMA(N)EMA-based devices. Furthermore, the suppression of degradation at the PDMA(N)EMA interface also improved device stability at elevated temperatures. This work highlights the importance of the design and development of appropriate interlayer materials for realizing stable and high-efficiency nonfullerene-based OPVs.
Keywords: NON-FULLERENE ACCEPTOR; PERFORMANCE; LAYER; ELECTRODES; DESIGN; FILM